Effects of AlN on the reactive sintering of porous Al2TiO5composites - Kitiwan, Mettaya; Kongsak, Mongkol; Atong, Duangduen; Wakui, Yoshito (My University, 2020)
The porous Al2TiO5/Al2O3 composites were fabricated by reactive sintering at 1500-1700 °C in nitrogen atmosphere. The starting materials Al2O3 and TiO2 were mixed in an equimolar ratio and the addition of AlN was 5-40 mol%. The effects of AlN content and sintering temperature on phase composition, linear shrinkage, pore sized distribution, porosity and microstructure were investigated. The XRD results showed that the composites mainly consist of Al2TiO5 while the peak intensity of Al2O3 increased with AlN content. The median pore sizes decreased with increasing AlN content and were in the range of 2- 6 lm, 1-2 lm, 0.4-0.7 lm, and 0.3-0.5 lm for composites using 10, 20, 30, 40 mol% AlN, respectively. The porosities of ATN10 and ATN20 were from 20% to 10% at 1600 °C to 1700 °C while the porosities of ATN30 and ATN40 were almost constant in between 11 and 13%. The addition of AlN effectively decrease the grain size of Al2TiO5 and led to reduce microcrack at the grain boundary.
Keywords: Alumina; Aluminum nitride; Aluminum titanate; Porous ceramic; Titanium dioxide